Interaction of Supply Chain Management, Entrepreneurship and Consumer Behaviour - Rakibovna Khayrullina, Yulduz; Rafisovna Garipova, Regina; Ivanovich Tyulenev, Alexander; Rudikovich Yamilov, Eduard; Ildusovna Nalimova, Elina (International Journal of Supply Chain Management, 2020)
Abstract— The role of supply managers in driving corporate performance is changing, with an increased emphasis on supply market intelligence, collaboration, inter-organizational partnerships, and operational integration with supply partners. The problem posed in the paper relates to the relationship of three important processes developing in modern society, namely: entrepreneurial activity, the consumer behavior, and supply chain management. The paper presents data from authors' expert surveys conducted in the Republics of Tatarstan and Mari El (2018) regarding the level of development of supply chain management, and consumer opportunities as an important indicator of the degree of wealth and entrepreneurial activity. It is concluded that the level of supply chain management of the population and individual social and professional groups is mainly medium, sometimes low, which impedes the development of entrepreneurial initiative improving the purchasing potential and quality of life of the population in the region. The paper provides recommendations on stimulating the growth of public confidence as a factor in the growth of consumer opportunities of the population with the goal of sustainable socio-economic development.